2015
DOI: 10.1016/j.tics.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The Rediscovery of Slowness: Exploring the Timing of Cognition

Abstract: Slowness of thought is not necessarily a handicap but could be a signature of optimal brain function. Emerging evidence shows that neuroanatomical and dynamical constraints of the human brain shape its functionality in optimal ways, characterized by slowness during task-based cognition in the context of spontaneous resting-state activity. This activity can be described mechanistically by whole-brain computational modeling that relates directly to optimality in the context of theories arguing for metastability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 79 publications
6
92
0
Order By: Relevance
“…Instead, like a Trojan horse, cuteness opens doors that might otherwise remain shut. In terms of mechanisms, we proposed that cuteness ignites activity in metastable brain networks, which provides a framework for sustaining the slowness inherent to prosocial behaviours [91]. Cuteness encourages caregiving and carefree playfulness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, like a Trojan horse, cuteness opens doors that might otherwise remain shut. In terms of mechanisms, we proposed that cuteness ignites activity in metastable brain networks, which provides a framework for sustaining the slowness inherent to prosocial behaviours [91]. Cuteness encourages caregiving and carefree playfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Survival-relevant positive cuteness as well as negative stimuli, such as infants’ crying, have been shown to selectively bias our attention through rapid activity in the orbitofrontal cortex which is then followed by slower, sustained processing in wider brain networks associated with emotion appraisal [14, 15, 58]. Importantly, significant progress has been made in understanding the dynamics of functional brain networks [91], and in particular the state-dependent coupling that is fundamental to implementing flexible effective communication between different brain regions—without changing the fixed underlying structure of the brain [92]. …”
Section: Putative Brain Mechanisms Of Cutenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms that enable humans to understand the emotions and actions of others function through online crosstalk between bottomup and top-down processes, fast sensory-motor integration and slower sociocognitive predictions (23,28), with specific dynamics defining distinct end products. Top-down processes are shaped by prior learning, attentional demands, regulatory abilities, and social goals, and authors have suggested that brain oscillations provide a useful vantage-point to tap the balance of bottom-up automaticity and top-down-regulation in understanding social phenomena (21).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-brain data from fMRI or MEG [46,47], and large-scale simulations of the brain based on tractography studies [47,48], provide evidence for rapid transitions between a few discrete functional connectivity states in the resting state of humans. These transitions and the underlying discrete states would not be revealed by time-averaged data [4749].…”
Section: Evidence For Multiple Attractor States and Itinerancymentioning
confidence: 99%